How Does Marketing Training Influence Students’ Knowledge and Skills in Developing Santripreneurship Within Islamic Boarding Schools? - Yani Qoriati; Akhmad Al-Bari; Romadhiyana Kisno Saputri; Siti Khoirun Nisak (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This study examines the influence of marketing training on students’ knowledge and skills in developing santripreneurship within Islamic boarding schools (pesantren). Despite the significant potential of pesantren as centers of community-based economic empowerment, many student-led business units face constraints, particularly in product marketing, which limits their competitiveness and sustainability. To address this issue, a structured marketing training program was conducted at Adnan Al Charish Islamic Boarding School, focusing on soap product development, packaging, labeling, and digital marketing strategies. The study employed a Participatory Action Research (PAR) approach involving 25 students through stages of planning, action, observation, and reflection. Data were collected using pre-tests, post-tests, observations, and satisfaction surveys. The findings reveal a substantial improvement in both knowledge and practical skills, with 84% of participants achieving a “very good” level in knowledge and 92% in skills after the training. Additionally, 88% of participants reported being “very satisfied,” indicating the high relevance and effectiveness of the training program. These results demonstrate that participatory and practice-based learning approaches effectively enhance students’ competencies, confidence, and ability to apply marketing strategies, particularly in utilizing digital platforms to expand market reach. In conclusion, marketing training plays a vital role in strengthening santripreneurship by improving students’ capabilities. However, continuous mentoring, advanced training, and long-term evaluation are necessary to ensure sustainability and maximize the impact of such programs.